Factors affecting the status of continuing nursing education in Sindh (Pakistan) - Gonsalves, Antoinette
It is argued that continuing nursing education (CNE) is one of the main factors that prevent obsolescence in nursing practice. The review of available literature has emphasized the importance of CNE and identified factors that enhance and deter participation in CNE in developed countries such as age, position, education, time, cost etc. In addition, research in CNE has identified the need for professionals to acknowledge CNE as a way of life. Hence the intent of this study was to see if the same holds true in Sindh, Pakistan.The purpose of this study was to determine the status of CNE in Sindh, to identify the factors that affect participation in CNE and to explore the factors that inhibit planning and implementation of CNE in Sindh.A descriptive cross-sectional survey design was utilized. An institutional based cluster sampling methodology with a sample of 200 was determined using the formula for unmatched and cross-sectional studies. This study was conducted in private and government hospitals and schools of nursing in the province of Sindh (Pakistan). The subjects were randomly selected using a fish bowl method of selection. A total of 176 nurses and 20 directors/matrons were inteviewed in 22 hospitals. Two self designed interview guides were developed and pilot tested. The data was then analysed using descriptive (frequencies and means) and inferential statistics (chi-square and logistic regression).An 88response rate was obtained. Findings implied that variables which were not statistically significant to participation in CNE were: age, marital status, child dependency, educational preparation, years of service in the present institution, incentives, and years of experience. However, the variables that were significant related to participation in CNE were: the year nurses received their last diploma, type of institution in which they worked and self-directed learners (nurses who used the library and were regularly read nursing books).Logistic regression was used to summarize the results.